CONCEPTS AND CLASSIFICATION OF SOCIAL INNOVATIONS IN THE SPHERE OF HOTEL AND RESTAURANT BUSINESS - Пересічна, Світлана; Корбачова, Дар’я (Modern engineering and innovative technologies, 2023)
The article examines the concept of social innovation in the field of hotel and restaurant business as a separate type of innovative activity, in particular, the differences between the main concepts such as social innovation, social responsibility of bu